Mechanism of material deformation during cavitation bubble collapse. (August 2021) - Sarkar, Prasanta; Ghigliotti, Giovanni; Franc, Jean-Pierre; Fivel, Marc
Abstract: This research is devoted to understanding the physical mechanism of cavitation erosion in liquid flows at the fundamental scale of cavitation bubble collapse. Cavitation bubbles form in a liquid when the pressure of the liquid decreases locally below the saturated vapor pressure p v s a t . The bubbles grow due to low ambient pressure and collapse when the surrounding liquid pressure increases again above p v s a t . Bubble collapse near solid walls can result in high velocity liquid jet and shock wave emission that cause high pressure loads on the wall. These pressure loads are responsible for the erosive damages on solid surfaces, as observed in applications like liquid fuel injection, hydrodynamic power generation and marine propulsion. On the other hand, the pressure loads from collapsing bubbles are exploited for applications like shock wave lithotripsy, drug delivery and cleaning surfaces. In this work, we follow a numerical approach, which begins with the development of a compressible solver capable of resolving the cavitation bubbles in the finite-volume code YALES2 1 employing a simplified homogeneous mixture model. The solid material response to cavitation loads is resolved with the finite element code Cast3M 2 . A one–way coupling approach for fluid–structure interaction (FSI) simulation between the fluid and solid domains is pursued. In this simple approach, the pressure field computed by the fluid solver at the fluid–solid interface is communicated to the solid solver which computes the deformation induced in the material. In the end, the dynamical events responsible for surface deformation are highlighted from 2D vapor bubble collapse dynamics and associated pressure loads on the solid wall are estimated. The response of different materials to bubbles collapsing at different distances from the solid wall is discussed.